2006
DOI: 10.1128/mcb.00506-06
|View full text |Cite
|
Sign up to set email alerts
|

The Ral/Exocyst Effector Complex Counters c-Jun N-Terminal Kinase-Dependent Apoptosis in Drosophila melanogaster

Abstract: Ral GTPase activity is a crucial cell-autonomous factor supporting tumor initiation and progression. To decipher pathways impacted by Ral, we have generated null and hypomorph alleles of the Drosophila melanogaster Ral gene. Ral null animals were not viable. Reduced Ral expression in cells of the sensory organ lineage had no effect on cell division but led to postmitotic cell-specific apoptosis. Genetic epistasis and immunofluorescence in differentiating sensory organs suggested that Ral activity suppresses c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 79 publications
3
51
0
Order By: Relevance
“…In Drosophila, the Ral-Exocyst-Msn-JNK cascade regulates developmental-induced apoptosis [26]. In mammals, RalA mediates TNF-α-induced p38 MAPK activation, and oxidative stress-induced FOXO activation, suggesting that RalA may regulate stress responses [26,31].…”
Section: Rala Map4k4 and Ndr1 Mediate Stress-activated P38 Kinase Phmentioning
confidence: 99%
See 2 more Smart Citations
“…In Drosophila, the Ral-Exocyst-Msn-JNK cascade regulates developmental-induced apoptosis [26]. In mammals, RalA mediates TNF-α-induced p38 MAPK activation, and oxidative stress-induced FOXO activation, suggesting that RalA may regulate stress responses [26,31].…”
Section: Rala Map4k4 and Ndr1 Mediate Stress-activated P38 Kinase Phmentioning
confidence: 99%
“…MAP4K4 has been defined as a Stress-Activated MAP Kinase (SAPK), driving the activation of MAPK-JNK cascades [22,29,30]. In Drosophila Msn, the fly counterpart of MAP4K4 [28], is part of a Ral-Sec5-Msn-JNK cascade regulating developmentalinduced apoptosis [26]. However, the role of MAP4K4 as signaling partner of RalA and/or RalB has not been defined yet in human cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Another study using sec5 mutants showed that through the exocyst effector, Ral regulates JNK signaling and p38 MAPK to prevent apoptosis in sensory organ precursor cells. 13 Although there has not yet been a genetic analysis of RalBP1 effector function, Drosophila Ral does bind in vitro to RalBP1 as well to Sec5. 16 We recently discovered a specific role for Drosophila Ral in Notch signaling.…”
Section: Ral Inhibits Ligand-independent Notch Signaling In Drosophilamentioning
confidence: 99%
“…[5][6][7][8] Through the exocyst, Ral regulates many cellular processes including secretion, 4 cytokinesis, 9 cytoskeletal remodeling, 10,11 membrane remodeling, 12 and apoptosis. 13,14 There are two separate Ral genes in vertebrates, RalA and RalB, which produce proteins comparable in amino acid sequence (81% identical and 89% similar) and organization of functional units. 1,15 RalA and RalB have different cellular functions through RalA-specific and RalB-specific RalGEFs.…”
Section: Introductionmentioning
confidence: 99%